Hybrid Coronary Revascularization Using Coronary Artery Bypass Grafting via Left Anterior Small Thoracotomy (Single Center Experience) - O. V. Pyetkov; I. V. Polivenok; Yu. M. Skibo; O. V. Buchneva; V. V. Boyko (Ukrainian Journal of Cardiovascular Surgery, 2017)
Hybrid coronary revascularization (HCR) combines such advantages of coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) as durable long-term result and low periprocedural risks.Objective. To analyze of results of HCR using the minimally invasive direct coronary artery bypass grafting (MIDCAB) on the basis of single center experience.Materials and methods. Thirty patients underwent MIDCAB with left internal thoracic artery to left anterior descending (LAD) via left anterior small thoracotomy. HCR was performed in eight of them.Results and discussion. There were no conversions, in-hospital mortality and perioperative myocardial infarctions in the study group. Poor thoracotomy wound reparation was the main complication (and the main disadvantage) that occurred in 8 (27%) patients (seven of them presented with diabetes mellitus or obesity) but with no long-term adverse consequences. In late follow-up period one death occurred for unknown reasons in 13 months after MIDCAB. One patient experienced a relapse of angina in 4 years after HCR due to the stent occlusion.Conclusions. MIDCAB is still a preferable alternative to PCI in patients with complex LAD lesions especially in centers with limited resources. It also could be used as a stage in HCR in such centers especially in patients with additional risks or limitations for traditional CABG.